2016
DOI: 10.1039/c5cs00651a
|View full text |Cite
|
Sign up to set email alerts
|

Solution based CVD of main group materials

Abstract: This critical review focuses on the solution based chemical vapour deposition (CVD) of main group materials with particular emphasis on their current and potential applications. Deposition of thin films of main group materials, such as metal oxides, sulfides and arsenides, have been researched owing to the array of applications which utilise them including solar cells, transparent conducting oxides (TCOs) and window coatings. Solution based CVD processes, such as aerosol-assisted (AA)CVD have been developed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 266 publications
(497 reference statements)
2
162
0
Order By: Relevance
“…Aerosol-assisted chemical vapor deposition (AACVD) is a simple and easily scalable technique that operates at ambient pressure. 32,33 Precursors for AACVD are dissolved in a suitable solvent and delivered to the CVD chamber in the form of aerosol droplets. As such, the precursors need not be volatile, only soluble in a suitable solvent.…”
mentioning
confidence: 99%
“…Aerosol-assisted chemical vapor deposition (AACVD) is a simple and easily scalable technique that operates at ambient pressure. 32,33 Precursors for AACVD are dissolved in a suitable solvent and delivered to the CVD chamber in the form of aerosol droplets. As such, the precursors need not be volatile, only soluble in a suitable solvent.…”
mentioning
confidence: 99%
“…65,66) However, due to the high operating temperatures, most published studies on AACVD refer to the production of inorganic NC coatings in which for instance the inorganic NPs are embedded in a host metal oxide matrix. 65,66) Interestingly, recently it was shown that the adequate choice of the organic component (e.g., a thermosetting silicone elastomer) 67) and of the temperature allows avoiding the pyrolytic decomposition of the organic fraction and affords the deposition of an organic-inorganic NC coatings. In this context, the aerosol-assisted atmospheric cold plasma deposition from dispersions containing inorganic NPs and the liquid organic precursor represents a promising approach, since the deposition occurs in a single step and at room temperature.…”
Section: Aerosol-assisted Deposition Of Hydrocarbon Polymer/zno Nanopmentioning
confidence: 99%
“…Recent research has highlighted the importance of careful precursor design, in order to facilitate cleaner decomposition, 22 lowering contamination and improving performance of the resultant functional material. Chemical vapour deposition (CVD) has drawn attention as a method to synthesis thin lms of functional materials, 23 including metal selenides. 24,25 The use of single source precursors in CVD has a number of advantages, not least the simplication of the decomposition mechanism since all required elements are delivered to the desired substrate at the same time.…”
Section: 17mentioning
confidence: 99%
“…[1][2][3][4][5] The design of high-efficiency materials which can convert solar to electrical energy is a continuously increasing research topic, in which the main path nowadays involves thin-lm technology. 6 Early transition metal chalcogenides have been reported to have applications as cathode materials for rechargeable batteries.…”
Section: Introductionmentioning
confidence: 99%